The Biopolitics of Thirdspace: Urban Segregation and Resistance in Puerto Rico's Luis Lloréns Torres Public Housing Project. Issue 1 (2nd January 2016) - Oliver-Didier, Oscar
Abstract: The public housing programme in Puerto Rico was highly influenced by a culturally engrained logic of colonialism that aimed to achieve a behavioural transformation of the residents of public housing based on white "criollo" norms and conducts. To this day, the process of Othering with which these bodies are understood and viewed has recurrently been reproduced and redeployed utilizing the island's old racial/colonial hierarchies. Criminality and drug-related activities are the main discursive agents employed to stigmatize the communities that live inside public housing in Puerto Rico. It is constantly inferred that most of its residents break with the behavioural norms that the rest of the population abides by. This argument is constantly utilized to perpetuate the cultural lens that views these sectors as lazy, unruly and dangerous. This highly prejudiced misconception justified the police occupations and the fences that were erected in and around public housing premises during the 1990s. However, most of these communities rarely view themselves as victims, and it is this paper's argument that they are constantly and collectively enacting political and physical spaces of dissent, resistance and encounter that – however momentarily – are able to overturn some of these powerful ideological and spatial constructs.